English relations with the Ottoman province of Tunis, prospects for conflict and alliance (1623-1762) (Journal of the College of Basic Education, 2022)
This research sheds light on an important era in the history of the Ottoman province of Tunisia and its external relations, specifically its relationship with England at the beginning of the modern era. It aims at forming a comprehensive picture of the dimensions of this relationship that swayed between peace and war and the interests and benefits of England from those relations in the context of its struggle with other European powers competing with it, when England had just begun during the reign of Queen Elizabeth (1558-1603) to build a young colonial commercial empire that competed fiercely with Spain and then With France in North Africa, This competition was often withdrawn to Tunisia and other spheres of influence around the world. Through this research, the researcher tried to clarify aspects of the relationship that linked the Ottoman province of Tunisia with England from its beginning in the first half of the seventeenth century until the end of the eighteenth century, by adopting a scientific, historical methodology based on analysis, conclusion, and comparison, to attain the truth that is based on the available sources